Acute effects of mental fatigue on resistance exercise volume - Lima Junior, Dalton Roberto Alves Araujo de (2022)
The prolonged mental effort caused by cognitive tasks, which usually comprises activities requiring attention, inhibitory control, and boredom or monotony, might cause a phenomenon known as mental fatigue (MF). Studies have shown that MF reduces cognitive and physical performance in recreational and professional athletes. In the literature, several cognitive tasks that induce MF might be observed. Some of them, such as social networks on smartphones and video games, are commonly used before training and matches. Although the literature presents a large body of evidence in MF's effects on endurance performance, whether MF reduces volume in an RE session is still unclear. Once RT is the main method to increase muscle mass and strength and those adaptations are desired by a wide range of individuals (i.e., from athletes to older people), verifying the possible deleterious effects of MF on RT is vital. Thus, the aim of the thesis is to analyze the acute effects of MF in the resistance exercise volume. The thesis is divided into two studies. In the study one, a systematic review with meta-analysis was conducted to evaluate and quantify the effect of MF on the RE volume. We observed with moderate-quality level of evidence that MF reduces RE volume. In the study two, 18 participants participated into two conditions: documentary and Stroop task (STROOP). Following, the participants performed three sets of half back-squat to failure, with intensities of 50, 70, and 90% 1RM. The number of repetitions were significant lower for the 50 (p<.05) and 75% 1RM (p<.05) in the mental fatigue condition, but the 90% 1RM remained similar (p>.05). Also, the perceived effort showed significant higher results for the 50 (p<.05) and 75% 1RM (p<.05) in the mental fatigue condition, but the 90% 1RM remained similar (p>.05). We conclude that similarly to endurance exercise, resistance exercise is negatively affected by MF in light- and moderate-intensity loads with repetitions to failure.